2008
DOI: 10.1093/aob/mcn007
|View full text |Cite
|
Sign up to set email alerts
|

Apple Dwarfing Rootstocks and Interstocks Affect the Type of Growth Units Produced during the Annual Growth Cycle: Precocious Transition to Flowering Affects the Composition and Vigour of Annual Shoots

Abstract: These results showed that rootstocks/interstocks affect the type of growth units produced during the annual growth cycle, reducing the number of extension growth units, thus affecting the composition and vigour of annual shoots. This effect is particularly amplified by the transition to flowering induced by dwarfing rootstocks. The division of annual shoot into growth units will also be useful for measuring and modelling effects of age on apple tree architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 23 publications
6
40
0
Order By: Relevance
“…In the present study, the influence of rootstock and cultivar/rootstock interaction on TH was not significant. Similar findings were found by Seleznyova et al (2008), who reported that rootstocks did not affect on TH of young apple trees during the first year after budgrafting. The results conformed to those for pear reported by Jacyna (2004).…”
Section: Analysis Of Nursery Tree Height and Trunk Diametersupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the influence of rootstock and cultivar/rootstock interaction on TH was not significant. Similar findings were found by Seleznyova et al (2008), who reported that rootstocks did not affect on TH of young apple trees during the first year after budgrafting. The results conformed to those for pear reported by Jacyna (2004).…”
Section: Analysis Of Nursery Tree Height and Trunk Diametersupporting
confidence: 89%
“…For apples and other fruit species, there are two major factors that can affect and consequently, alter the architecture and the overall size of fruit trees. The first one is the species and/or cultivar Lauri et al, 1995), and the second is the root system, studied from different standpoints, most commonly in terms of trees grafted on rootstocks (Seleznyova et al, 2008). Branching is a key factor in the evolutionary diversification of plants and a main criterion used in plant architecture analysis (Lauri, 2007), cultivar being the primary factor affecting the branching in fruit trees (Quinlan and Tobutt, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dwarfing rootstocks and inter-stems reduced the number of extension shoots and promoted the formation of floral shoots (Seleznyova et al , 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Regardless, spur-type apple cultivars undoubtedly moderately reduced tree size as compared to standard-type trees (Costes et al, 2010). Unlike dwarfing rootstocks that reduce the proportion of lateral buds that develop into long shoots during the early development of trees (Lauri and Trottier, 2006; Seleznyova et al, 2008), YF produces a dwarf tree architecture by reducing the duration of shoot vegetative growth and shortening internode length.…”
Section: Discussionmentioning
confidence: 99%